2012
DOI: 10.1100/2012/738314
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntibacterial and Time-Kill Evaluation of theErythrina caffraThunb. Extract against Bacteria Associated with Diarrhoea

Abstract: The antibacterial activities of stem bark ethanolic extract of Erythrina caffra Thunb. against bacteria in diarrhoea was determined in vitro by the agar diffusion and dilution, macrobroth dilution, and time-kill assay methods. The result showed that the extract produced inhibition zones ranging between 15 ± 1.0 mm and 23 ± 1.0 mm, and the bacteria were susceptible at concentrations ranging between ≤100 and ≤1000 μg/mL. While the MICs of the extract ranged between 39.1 and 625 μg/mL, and the MBCs ranged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
25
1
Order By: Relevance
“…Time kill assay was carried out as previously described [ 26 ]. Bacterial suspension (10 5 CFU/mL) was added to microplates along with peptide 8 at 6.25 μM MIC concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Time kill assay was carried out as previously described [ 26 ]. Bacterial suspension (10 5 CFU/mL) was added to microplates along with peptide 8 at 6.25 μM MIC concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Minimum bactericidal concentration (MBC) assay MBC was defined as the lowest concentration of the samples wherein no visible turbidity or colonies were observed. [17] In order to determine the MBC, the solution for concentration being tested was spread on sterile PCA (Oxoid, Basingstoke, Hampshire, England) plates and incubated at 37°C for 24 h. This was done for all three bacterial strains in triplicate.…”
Section: Minimum Inhibitory Concentration (Mic 50 ) Assaymentioning
confidence: 99%
“…These results suggests that this plant might contain bioactive compounds that act as antimicrobial and antioxidant agents. It has been reported that in vitro tests do not necessarily confirm that the plant extracts are effective drugs or a suitable candidate for drug development, it provides a basis for understanding the effectiveness of the plant and leads in particular to the search for new active substances [ 10 ]. Therefore, the aim of this study was to isolate bioactive compound from A. ataxacantha barks and investigate their antimicrobial and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%